Pengaruh Pemberian Kadar Bertingkat Ekstrak Daun Ruku-Ruku Hutan (Ocimum Sp) Terhadap Penyembuhan Luka Sayat Pada Mencit - Abeiasa, M. Saka; Ardika, Eche; Mossfika, Eldya (Universitas Sumatera Barat, 2022)
Wound is a state of loss of continuity of tissue structure. Cut injury is an injury caused by being cut by an instrument sharp objects such as knives, razors, mirrors, and other sharp objects. Rukuruku forest is one of the ingredients of traditional medicine that has many properties as anti-bacterial, anti-inflammatory, anti-cancer, anti-fungal and has the effect of anti-oxidant activity. Rukuruku forest leaves contain flavonoid compounds, tannins, saponins, and essential oils that can speed up the treatment of injuries. The content of essential oils acts as an antibacterial, antimicrobial, antiseptic, anti-inflammatory, antioxidant. This research aims to identify the effect of